Cycling time trial performance is improved by carbohydrate ingestion during exercise regardless of a fed or fasted state. (17th February 2019) - Learsi, Sara K.; Ghiarone, Thaysa; Silva‐Cavalcante, Marcos D.; Andrade‐Souza, Victor A.; Ataide‐Silva, Thays; Bertuzzi, Romulo; de Araujo, Gustavo G.; McConell, Glenn; Lima‐Silva, Adriano E.
Abstract : Purpose: We tested the hypothesis that carbohydrate ingestion during exercise improves time trial (TT) performance and that this carbohydrate‐induced improvement is greater when carbohydrates are ingested during exercise in a fasted rather than a fed state. Methods: Nine males performed 105 minutes of constant‐load exercise (50% of the difference between the first and second lactate thresholds), followed by a 10‐km cycling TT. Exercise started at 9am, 3 hours after either breakfast (FED, 824 kcal, 67% carbohydrate) or a 15‐hour overnight fast (FAST). Before exercise, after every 15 minutes of exercise and at 5 km of the TT, participants ingested 2 mL kg −1 body mass of a non‐caloric sweetened solution containing either carbohydrate (8% of maltodextrin, CHO) or placebo (0% carbohydrate, PLA). Results: Irrespective of the fasting state, when carbohydrate was ingested during exercise, the rating of perceived exertion (RPE) was lower throughout the constant‐load exercise, while the plasma glucose concentration and carbohydrate oxidation were higher during the last stages of the constant‐load exercise ( P <  0.05). Consequently, TT performance was faster when carbohydrate was ingested during exercise (18.5 ± 0.3 and 18.7 ± 0.4 minutes for the FEDCHO and FASTCHO conditions, respectively) than when the placebo was ingested during exercise (20.2 ± 0.8 and 21.7 ± 1.4 minutes for the FEDPLA and FASTPLA conditions, respectively), regardless of fasting. Conclusion: These findings indicate that even when breakfast is provided before exercise, carbohydrate ingestion during exercise is still beneficial for exercise performance. However, ingesting carbohydrate during exercise can overcome a lack of breakfast.